2013
DOI: 10.1007/s00213-013-3011-2
|View full text |Cite
|
Sign up to set email alerts
|

The atypical antipsychotic risperidone reverses the recognition memory deficits induced by post-weaning social isolation in rats

Abstract: Similar to its clinical profile, risperidone only partially reverses the schizophrenic symptomology; since it reversed some, but not all, of the learning and memory deficits induced by post-weaning isolation, the isolation rearing model may be useful to predict antipsychotic activity of novel therapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 67 publications
6
21
0
2
Order By: Relevance
“…Both isolation-rearing (Jones et al, 2011; Watson et al, 2012; McIntosh et al, 2013) and repeated PCP-injection to adult rats (McKibben et al, 2010; Grayson et al, 2015) impair NOR, as does combined PCP-SI (Gaskin et al, 2014; Watson et al, 2016), consistent with findings in this study. Lamotrigine at the low (10mg/kg i.p.)…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Both isolation-rearing (Jones et al, 2011; Watson et al, 2012; McIntosh et al, 2013) and repeated PCP-injection to adult rats (McKibben et al, 2010; Grayson et al, 2015) impair NOR, as does combined PCP-SI (Gaskin et al, 2014; Watson et al, 2016), consistent with findings in this study. Lamotrigine at the low (10mg/kg i.p.)…”
Section: Discussionsupporting
confidence: 89%
“…Despite there being no overall significant effect of lamotrigine on locomotor activity [F (2,31) = 2.985, p = 0.065], there was a significant housing x drug interaction [F (1,31) = 5.501, p = 0.025] over the 60min session, reflecting a reduction in activity due to lamotrigine treatment in the isolation-reared animals only (Figure 1A). Furthermore, two-way ANOVA of total activity during the first 30min (where activity differences were most marked, as often found in isolation studies; Bianchi et al, 2006; Fabricius et al, 2010; McIntosh et al, 2013) revealed a significant rearing x drug interaction [F (1,32) = 6.719, p = 0.014], but no main effect of either rearing condition or drug treatment alone (Figure 1B). Of note, post hoc analysis confirmed there was a significant increase ( p < 0.05) in locomotion in PCP-SI-V compared to control V-GH-V rats, which was significantly reduced ( p < 0.05) by the highest dose of lamotrigine (PCP-SI-L15) compared to that in PCP-SI-V rats.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…al. study, from P19 to P73, compared to P28 to P52 in the current study, and longer lasting isolation has been accompanied by learning deficits [25] and amotivation for social interaction [57]. Second, the study of Hermes et al used female rats, which could indicate sex differences in the effects of isolation rearing on mPFC PSD-95.…”
Section: Discussionmentioning
confidence: 71%
“…The SA is limited in this regard as the stimulus animal is confined to a cage, and while CPP allows for behavioral monitoring during training, the later testing phase prohibits harvesting tissue within relevant time frames to examine immediate early gene expression in response to the social behavior, which occurs within a timeframe between 1 and 2 hours [24]. Additionally, the use of “escapable” social interaction may provide a direct measure of social interaction-seeking behavior reflective of motivational drive in the absence of a learned association with a specific environment as in CPP, which may be confounding in ISO rats as PSI induces learning deficits [25]. Furthermore, the ESIT allows for the manipulation of the behavioral phenotype of the stimulus rat.…”
Section: Introductionmentioning
confidence: 99%